2021
DOI: 10.1080/08974454.2021.2019653
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Poor Health among Workers in Criminal Justice, Community and Social Services, and Healthcare: Adverse Childhood Experiences, Workplace Trauma Exposure, and Gender Differences

Abstract: Adverse childhood experiences and workplace trauma exposure are associated with poor health.However, their differential impacts by gender are difficult to assess in studies of organizations with gender imbalances (e.g., law enforcement officers are more likely men whereas social workers are more likely women). Using a community-based participatory research framework, this study examines trauma exposure, mental and physical health, and substance use in an occupationally diverse sample (n=391).Trauma exposure wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Likewise, research on the culture of law enforcement has shown that cynicism is high among law enforcement officers (Alves et al, 2023). Lastly, the culture of community-based organizations is that women tend to be over-represented in this work (Knight et al, 2021; McPhail, 2004) and, in general, women have higher rates of PTSD compared to men (Valentine et al, 2019). Ultimately, we recommend educating organizations about these differences and encouraging them to use evidence-based organizational improvement processes (Hallinan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, research on the culture of law enforcement has shown that cynicism is high among law enforcement officers (Alves et al, 2023). Lastly, the culture of community-based organizations is that women tend to be over-represented in this work (Knight et al, 2021; McPhail, 2004) and, in general, women have higher rates of PTSD compared to men (Valentine et al, 2019). Ultimately, we recommend educating organizations about these differences and encouraging them to use evidence-based organizational improvement processes (Hallinan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, our findings align with the theoretical perspectives that informed this study. This includes our prior research (Knight et al, 2018, 2021, 2022) and the conceptual model of secondary trauma (Ellis & Knight, 2021) that is based on Stern’s (1985) theory of the core self. Applying this theoretical framework of interpersonal trauma, findings from this study can be used to support policies and practices that enhance employees’ trust in themselves (i.e., self-agency), and trust in others (i.e., coherence of others), presence and mindfulness (i.e., self-affectivity), as well as professional growth over time (i.e., self-history).…”
Section: Discussionmentioning
confidence: 99%